City tourism : national capital perspectives - Maitland, Robert (CABI, 2015)
City tourism has grown rapidly and spread well beyond tourist-historic cities and resorts. With a focus on city tourism themes, this book draws on original research to investigate tourism in national capitals, considering image and branding, the visitor experience, visitor markets and tourism development.